Second-chance bodyguard - Sargeant, Patricia (Sargeant, Patricia. Touré Security Group, 2024)
"Hezekiah Touré cares about two things: looking after his younger brothers and managing the Touré Security Group. To protect his family, he agrees to go into hiding with Celeste Jarrett after a serial killer threat. As a private investigator, Celeste has information Zeke's family can use. As a woman he tried to love, she's always been hard to reach. Sharing a safe house might lead to sharing her bed, but can he convince her to trust him? Or will the wounds she suffered in the past drive them apart again?"--